Challenges and outcomes in establishing a sentinel lymph node biopsy service for oral squamous cell carcinoma in a regional district specialist hospital. Issue 2 (February 2021) - Bowe, C.M.; Shastri, M.; Gulati, A.; Norris, P.; Corrigan, A.; Barrett, A.W.; Bisase, B.
Abstract: UK national guidelines in 2016 recommended that sentinel lymph node biopsy (SLNB) should be offered to patients with early oral squamous cell carcinoma (OSCC). We review the establishment of an OSCC SLNB service with specific consideration to resources, service implications and patient outcomes. A review of processes was performed to identify key stages in establishing the service, and subsequently a retrospective cohort study consisting of 46 consecutive patients with T1/T2 N0 OSCC was undertaken. The key stages identified were: coordinating a nuclear medicine pathway and reliable cost-appropriate pathology service, constructing a Trust business case, and gaining approval of a new interventional service policy. A median (range) of 3.3 (1-8) sentinel nodes (SLN) were removed, with 17 patients having a positive SLN. The negative predictive value of SLNB was 100%, with 12 having a SLN outside the field if elective neck dissection (END) was planned. There was a significantly increased risk of a positive SLN with increasing depth of invasion (DOI) (p=0.007) and increased diameter (p=0.036). We also identified a longer-than-ideal time to completion neck dissection and inadequate ultrasound follow up of negative SLNB patients. Establishment of a service requires careful planning. Our results were in keeping with those reported in the literature, and showed that SLNB for OSCC has a high negative predictive value and can identify at-risk SLN outside the traditional END levels, even in well-lateralised tumours. Our findings show that DOI and size of SLN were significantly associated with a positive SLN, and also identified areas requiring improvement.